Competency Diskomlek Koarmada I Personnel and its Implications For The Reliability of VSAT Systems on Republic of Indonesia Warships (KRI) - Zainul Arif Akbar; Daniel Guyana; Hanjar (National Research and Innovation Agency (BRIN Publishing), 2026)
The operational readiness of Indonesian Navy warships (KRI) depends heavily on the reliability of Very Small Aperture Terminal (VSAT) systems, which serve as the backbone of satellite communication in naval operations. This study aims to analyze the competency of Communication and Electronics Service (Diskomlek) personnel at the First Fleet Command (Koarmada I) in maintaining VSAT systems and its implications for system reliability. A qualitative approach with an intrinsic case study design was employed, involving 18 purposively selected participants. Data were collected through semi-structured in-depth interviews, participant observation, and document analysis, then analyzed using NVivo 14. The findings reveal that personnel competency encompasses three dimensions: technical knowledge, practical skills, and professional attitude. Strengths lie in theoretical knowledge and discipline in preventive maintenance, while weaknesses are found in advanced practical skills, independent troubleshooting capabilities, and proactive fault detection. Corrective maintenance faces challenges due to prolonged repair times, with modem failures reaching 24 incidents annually (mean repair time 8.5 hours) and antenna failures reaching 15 incidents annually (mean repair time 12 hours). Organizational factors, including limited spare parts availability, training systems insufficiently oriented toward practical needs, and personnel rotation policies disrupting expertise continuity, further weaken the relationship between competency and system reliability. This study concludes that capacity building through continuous education, simulation-based training, technical certification, and improved maintenance management systems is essential for ensuring communication reliability in naval operations.